The Implementation of Patient Safety Culture in Hospital: A Qualitative Research (International Journal of Nursing Education, 2023)
This study explores the implementation of patient safety culture in one of General Hospitals in the central part of Aceh Province, Indonesia. The research used a qualitative method with a phenomenological design, collected data using in-depth interviews with eight participants in inpatient and outpatient rooms. The Collaizi method was used to analyze the data and produced three themes, namely: (1) conditions needed to improve the directing function, (2) leaders’ response and concern, and (3) team support and coordination in implementing patient safety. The results of this study indicate that the problem of implementing a patient safety culture needs to be considered by hospital management to improve patient safety. It is recommended that service leaders at the hospital improve the directing function to improve the implementation of patient safety culture and the quality of hospital services.
Keywords: Patient safety, leadership, communication, teamwork.